Electrical, dielectric and electrochemical characterization of novel poly(acrylic acid)-based polymer electrolytes complexed with lithium tetrafluoroborate - Ngai, Koh Sing; Ramesh, Subramaniam; Ramesh, Kasi; Juan, Joon Ching (Elsevier, 2018)
A series of novel poly(acrylic acid)-based polymer electrolytes with high conductivities at room temperature has been prepared and studied. Polymer electrolytes composed of poly(acrylic acid) (PAA) and lithium tetrafluoroborate (LiBF4) were prepared by means of solution casting. The effect of the addition of LiBF4 on the properties of the PAA-based electrolyte matrices was analysed and investigated using impedance spectroscopy. The optimized PAA-based solid electrolyte showed an electrochemical stability window of 3.2 V. Thermogravimetric analysis indicated that the incorporation of LiBF4 into PAA matrix enhances the thermal stability. The structural properties of polymer electrolytes were studied by using X-ray diffraction analysis.